2019
DOI: 10.3390/buildings9030062
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial and Temporal Variability of the Indoor Environmental Quality during Three Simulated Office Studies at a Living Lab

Abstract: The living lab approach to building science research provides the ability to accurately monitor occupants and their environment and use the resulting data to evaluate the impact that various components of the built environment have on human comfort, health, and well-being. A hypothesized benefit of the living lab approach is the ability to simulate the real indoor environment in an experimentally controlled setting over relatively long periods of time, overcoming a significant hurdle encountered in many chambe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 79 publications
0
24
0
Order By: Relevance
“…The ASHRAE Standard 55 widely measures thermal comfort [4,32,36] and should be done using occupant satisfaction surveys, point-in-time surveys and electronic sensors measuring the thermal environment [58]. ISO 7730 and ASHRAE 55 standardise a predictive mean vote (PMV) steady-state model [59] used for measuring thermal comfort.…”
Section: Predictive Mean Vote (Pmv)mentioning
confidence: 99%
See 2 more Smart Citations
“…The ASHRAE Standard 55 widely measures thermal comfort [4,32,36] and should be done using occupant satisfaction surveys, point-in-time surveys and electronic sensors measuring the thermal environment [58]. ISO 7730 and ASHRAE 55 standardise a predictive mean vote (PMV) steady-state model [59] used for measuring thermal comfort.…”
Section: Predictive Mean Vote (Pmv)mentioning
confidence: 99%
“…All but one study measured visual comfort using LUX only (Table 2). The exception [36], measured visual comfort using a combination of LUX and a measure of lighting colour, using the Wovyn Color Lux1000. Their approach measured the impact of blue light on sleep but also the effectiveness of window tinting on a room's ambient colour temperature by placing light sensors at desk level and in elevated positions.…”
Section: Visual Comfortmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that during the study operation these factors were in the normal range for a typical office building [ 92 ]. For more details on the measurement and assessment of these parameters in a living lab, please refer to [ 63 ].…”
Section: Lighting Configuration and Environmental Data Analysis Rementioning
confidence: 99%
“…A case study by The Carbon Trust, (2012) indicated that an extra £10/m2 in annual operating energy costs resulted due to the performance gap between predicted and actual performance of the building [21]. The evolving nature of the world paved the way for the introduction of various capacity-extending technology, including automated sensors [22], artificial intelligence (AI) [23], and digital models, including building information modelling (BIM) [24]. The integration of all the latter is the topic of various discussions on the practical and research arenas [25].…”
Section: Introductionmentioning
confidence: 99%